Centrifugal-Granulation-Assisted thermal energy recovery towards low-carbon blast furnace slag treatment: State of the art and future challenges. (1st November 2022) - Wu, Junjun; Tan, Yu; Li, Peng; Wang, Hong; Zhu, Xun; Liao, Qiang
Highlights: Global status of blast furnace slag including production and end uses was detailed. Working principle of CGATER and hierarchical structure of its R & D were overviewed. Advances in CGATER practices were included and analyzed at laboratory and pilot scale. Future challenges and possible solutions were pointed out. Abstract: The iron and steel industry (ISI) is pursuing technology breakthroughs to accelerate the transition towards carbon neutrality. Deep cut of CO2 emission involves with not only technological revolution of producing iron and steel, but also exploiting energy in byproducts and off-process wastes. Molten blast furnace slag (BFS), one of the largest high-temperature byproducts, remains the last untapped waste heat source in ISI. Of ever-increasing interest is the centrifugal-granulation-assisted thermal energy recovery (CGATER) from high-temperature BFS. This technique features waste energy harvest and vitreous slag utilization. Such striking merit opens up new possibilities of enabling more sustainable and greener iron and steel production, and makes CGATER one of the most promising technologies in the portfolio of ISI CO2 mitigation. Despite the rapid development of CGATER in last decade, most previous efforts were dedicated to understanding the CGATER physics and its closely allied matters. To date, large-scale implementation of CGATER has been little explored beyond the laboratory or pilot scale. It is imperative to provide a critical, timely review on the status of CGATER and most importantly, the challenges in its further deployment at industrial scale. This article first provides an inclusive figure of global BFS production and its versatile role in civil engineering. The working principle and research status of CGATER are detailed to highlight its strength and weakness. Future challenges towards the CGATER industrialization have been scrutinized. Other new-emerging technologies or concepts are also included.